Rheological studies of food materials - Lee, Jane Tian Bao (2018)
The aim of this report is to show the results and analysis on the study of the rheological properties of Bok Choy and Pumpkin. Food mixtures were prepared with various types and combinations of hydrocolloid and their rheological properties were measured using a rheometer. The rheological study shows how various food hydrocolloids affects the rheological properties of the food mixtures. The steady state experiment was performed to understand how the shear rate would affect the viscosity of the food mixtures with various combinations of food hydrocolloids. For understanding how the storage modulus (G’) and loss modulus (G”) were affected, dynamic experiments were carried out. Oscillation - Frequency test was conducted to see how well the food samples react with varying frequency. Oscillation – Amplitude test was conducted with fixed frequency and varying strain%. Recovery tests were conducted to observe how well the food mixtures can regenerate to its original viscosity after being subjected to shear. All experiments were conducted at 65°C to mimic the condition of food that will be printed immediately after cooking.